The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/02652030410001712736
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organochlorine pesticide levels in bovine fat from Mexico

Abstract: Organochlorine pesticides have been used in Mexico in agriculture as a seed dresser, in sanitation, in malaria control programmes and in livestock to combat ectoparasites. The pesticides applied drift to areas where cattle graze and plants grow. Because of their chemical stability, they accumulate in the lipid-rich tissues of the body. In the body, they circulate throughout all compartments and accumulate in adipose fat. The aim was to monitor the organochlorine pesticide levels in bovine muscle fat and kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
3
4
1
1
Order By: Relevance
“…Comparing the results of this study with previous data reported in 1996 (Waliszewski et al, 1996b) for bovine tissues, a decrease in p,p 0 -DDT was observed in kidney from 1,965.00 to 76.79 lg/kg lipid (25-fold), muscle from 1,571.00 to 143.67 lg/kg lipid (11-fold), lung, liver, and heart tissues (8-fold) from 2,713.00, 955.00, and 506.00 to 349.11, 123.61, and 66.53 lg/kg lipid, respectively, and adipose tissue 467.00 to 173.16 lg/kg lipid (2.7-fold). A slight decrease in p,p 0 -DDE was also observed in heart and muscle from lg/kg lipid and in lung tissues from 215.0 to 504.464 lg/kg lipid, and 60-fold in liver tissues from 5.0 to 303.94 lg/kg lipid.…”
Section: Pardío Et Al / Food Chemistry 135 (2012) 1873-1893supporting
confidence: 84%
See 3 more Smart Citations
“…Comparing the results of this study with previous data reported in 1996 (Waliszewski et al, 1996b) for bovine tissues, a decrease in p,p 0 -DDT was observed in kidney from 1,965.00 to 76.79 lg/kg lipid (25-fold), muscle from 1,571.00 to 143.67 lg/kg lipid (11-fold), lung, liver, and heart tissues (8-fold) from 2,713.00, 955.00, and 506.00 to 349.11, 123.61, and 66.53 lg/kg lipid, respectively, and adipose tissue 467.00 to 173.16 lg/kg lipid (2.7-fold). A slight decrease in p,p 0 -DDE was also observed in heart and muscle from lg/kg lipid and in lung tissues from 215.0 to 504.464 lg/kg lipid, and 60-fold in liver tissues from 5.0 to 303.94 lg/kg lipid.…”
Section: Pardío Et Al / Food Chemistry 135 (2012) 1873-1893supporting
confidence: 84%
“…The pattern of tissue contamination detected in this study was different to the contamination levels found in previous studies (Waliszewski et al, 1996b). In this 1996 study, lung tissue mean levels of aÀHCH (105.00 lg/kg lipid), bÀHCH (232.00 lg/kg lipid) and cÀHCH (163.00 lg/kg lipid) were significantly different (P < 0.05) to other tissues concentrations, and the mean residues detected in muscle were bÀHCH (310.00 lg/kg lipid) and cÀHCH (91.00 lg/kg lipid).…”
Section: Hexaclorociclohexane (Hch)contrasting
confidence: 82%
See 2 more Smart Citations
“…These results agreed with the results obtained by Moreno et al [8] , Waliszwski, et al [9] , Mallatou et al [10] , Ganzhang, et al [11] and Beseler et al [12] . ----------------------------------------------------------------- …”
Section: Endrine Ketone ± ±supporting
confidence: 83%